EVALUATION OF RAW MILK QUALITY ARRIVING TO THE STATE ENTERPRISE FOR DAIRY PRODUCTS IN BAGHDA - H. Jasim, A.; H.Najim, N.; K. Al-Murrani , W. (The Iraqi Journal of Veterinary Medicine, 1992)
The main objective of this study was to evaluate raw milk quality. This study was designed to obtain random sampling of raw milk at weekly intervals from road tankers arriving to the State Enterprise for Dairy Productrs. Besides that either cow’s milk or mixed (cow-buffalo) milk from Milk Reception and Collection Center in Abu-Ghraib village and buffalo’s milk samples from producer’s homes at the same village, on two climatic periods; the first was the summer period from August to the end of October, 1987; the second being winter period from December 1987 till the end of February 1988 . 330 milk samples were collected and analysis performed were microbiological examinations besides that adequacy of cleaning and sanitization of producer’s cans in the village was studied. Raw milk arriving to Abu-Ghraib dairy plant had significantly (p<0.05) higher total bacterial, coliform counts in summer season than in winter and higher counts of psychrotrophic bacteria and yeasts molds counts in winter summer with significant difference (p<0.01). There was no significant differences in total bacterial counts between cow’s and buffalo’s milk, this is true for both seasons. Effectiveness of cleaning and sanitizing containers (milk cans) was determined by flushing of a measured volume of sterile nutrient broth over the product contact surface. Data revealed that high microbial population were noted in the rinse solution of all equipments tested, such microbes metabolized nutrient residues on incompletely cleaned container’s surfaces that could initiate milk spoilage. These results necessating a better hygienic measurements and more educational programmes are needed to improve the quality of milk and its products.